Psihologija za varnostno področje - Areh, Igor (University of Maribor Press, 2017)
Psychology for Security. The book is primarily written for undergraduate students of criminal justice and security studies, allowing them to get a good grasp of most basic knowledge of contemporary psychology. Though a structural review of general psychology, it is an upgrade featuring topics and discussions on a variety of issues related to police work, eyewitness testimony, and court proceedings. It is a short presentation of diversity in forensic psychology, cognitive, emotional and motivational processes, personality, and the main findings in social psychology. Its most comprehensive chapter focuses on memory processes as viewed in terms of eyewitness memory and testimony. Most topics are enriched by the latest findings in traffic and forensic psychology.